Occular morbidity in children with allergic conjunctivitis: A rural urban survey. (2023)
Background: Allergic conjunctivitis occasionally may result in some ocular morbidities. This ranges from innocuous to severe forms of ocular disorders. Aim: This study reports and compares ocular morbidities among children with ocular allergies living in an urban and rural community. Materials and Methods: A comparative cross‑sectional study conducted in urban and rural schools among children aged 5–15 years using a multistage sampling method. Sociodemographic data, past ocular history, history of ocular allergies, and treatment were collected with an interviewer‑based questionnaire and were analysed using the Statistical Package for the Social Sciences (SPSS) software version 25. Descriptive analyses of sociodemographic variables and associated ocular morbidity were carried out. The Chi‑square test was used to test associations between rural and urban groups. A P = 0.05 or less was considered significant. Results: Associated ocular morbidities were seen in 8% (19/238) of the children with allergic conjunctivitis. There was no statistically significant difference in the proportion of ocular morbidities observed between both locations (8.1 vs. 7.9 in the rural and urban location, respectively, with a P = 1.000). Children with mild forms of allergic conjunctivitis were 197 (82.8%), and only 1.7% had severe forms. The moderate and severe form of allergic conjunctivitis were more prevalent in the rural area (P = 0.002) while untreated allergic conjunctivitis was found in 168 (70.6%) of those affected. Conclusion: This study demonstrated a higher proportion of moderate‑to‑severe forms of allergic conjunctivitis among school children in the rural region with the majority being untreated.